DK87: Et korpus med dansk almensprog - Bergenholtz, Henning (HERMES - Journal of Language and Communication in Business, 1988)
At the Aarhus School of Business a corpus of standard Danish has been established which contains 1 mio words divided into 200 texts of 5.000 words each. All the texts are original 1987 publications, 25% of them newspapers, 25% magazines and 50% fiction. Furthermore, three other corpora are under preparation: a corpus of Danish, French and English within the law of contract. The corpora are distributed free of charge to linguists under the following conditions: 1. The corpus may not be further distributed and 2. the corpus may not be used for commercial purposes. The corpus will be extended to a total of 5 mio words in the course of the coming five years.